A predictive policy model to forecast outcomes of drug development in developing countries. Issue 2 (22nd May 2019) - Siagian, Ria Christine; Besral, Besral; Achadi, Anhari; Ayuningtyas, Dumilah
Abstract : Purpose: The World Health Organization has pointed out that the majority of developing countries currently rely on imported drugs, in spite of the fact that there is potential for them to produce their own drugs. The purpose of this paper is to present a framework as an innovation policy model that can strategically predict the outcome of drug development investment in developing countries. Design/methodology/approach: In order to explore a model relevant to the policy-making process, the literature was systematically reviewed with a focus on the impact of policy changes on drug development in developing countries. Findings: An innovation policy model consists of the relational influences of contextual variables of pharma capabilities, innovation incentives and political factors affecting drug development in developing countries, derived from a dissenting policy-making perspective. This was built to test two hypotheses of a positive relationship between the above variables; and a perspectives gap between the pharmaceutical companies and the policymakers. These hypotheses address issues related to the lack of drug development in developing countries. Research limitations/implications: This paper presents a conceptual framework for the evaluation and provides examples of its use, but it is currently at a relatively early stage of research. Further work is currently underway and will later be presented to the same journal. Social implications: Domestic drug development in developing countries needs to be feasible in order to ensure drug security. This predictive policy model provides a comprehensive approach to health policy reforms to examine innovation strategies. Originality/value: This model includes measures to explore whether pharma capabilities, innovation incentives and/or political factors have an effect on domestic drug development in developing countries. It bridges the policy implementation's operational process between pharmaceutical companies and policymakers.